Breast Cancer Classification Based on Tumor Budding and Stem Cell-Related Signatures Facilitate Prognosis Evaluation - Xiang, Zhenxian; He, Qiuming; Huang, Li; Xiong, Bin; Xiang, Qingming (Frontiers in Oncology, 2022)
ABSTRACT Background: Tumor budding (TB) is emerging as a prognostic factor in multiple cancers. Likewise, the stemness of cancer cells also plays a vital role in cancer progression. However, nearly no research has focused on the interaction of TB and tumor stemness in cancer. Methods: Tissue microarrays including 229 cases of invasive breast cancer (BC) were established and subjected to pan-cytokeratin immunohistochemical staining to evaluate molecular expression. Univariate and multivariate analyses were applied to identify prognostic factors of BC, and the chi-square test was used for comparison of categorical variables. Results: High-grade TB was significantly associated with T stage, lymph node metastasis, tumor node metastasis (TNM) stage, Epithelial-mesenchymal transition, and poor disease-free survival (DFS) of BC patients. We also found that the prognostic value of TB varied widely among different subtypes and subgroups. Then, Cox regression analysis showed that TB grade was an independent prognostic factor. Moreover, cancer stem cells (CSCs) markers CD44 and ALDH1A1 were significantly higher in high-grade TB tumors. Consequently, patients were classified into high CSCs score subgroup and low CSCs score subgroups. Further research found that CSCs scores correlated with clinicopathologic features and DFS of BC patients. Based on TB grade and CSCs scores, we classified BC patients into TBlow -CSCslow (type I), TBlow-CSCshigh (type II), TBhigh -CSCslow (type III), and TBhigh -CSCshigh (type IV) subgroups. Survival analysis showed that patients in the type I subgroup had the best DFS, whereas those in the type IV subgroup had the worst DFS. Finally, a TB-CSCs based nomogram for use in BC was established. The nomogram was well calibrated to predict the probability of 5-yesr DFS, and the C-index was 0.817. Finally, the area under the curve value for the nomogram (0.892) was higher than that of the TNM staging system (0.713). Conclusion: The combination of TB grade with CSCs score improves the prognostic evaluation of BC patients. A novel nomogram containing TB grade and CSCs score provides doctors with a candidate tool to guide the individualized treatment of cancer patients.